Digital Marketing untuk Pengembangan UKM di Kecamatan Lumbir, Kabupaten Banyumas - Rini Widianingsih; Icuk Rangga Bawono; Indah Nuraeni; Irianing Suparlinah; Agus Sunarmo (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2025)
Lumbir Subdistrict in Banyumas Regency, Central Java, holds significant economic potential through various Small and Medium Enterprises (SMEs) sectors, including traditional food industries, handicrafts, garment production, as well as service and retail trade. However, the majority of SME actors still rely on conventional marketing methods and possess low levels of digital literacy, which limits the market reach of their products. This community engagement activity aims to enhance the capacity of SME actors in utilizing digital marketing through intensive training and mentoring. The methods employed include needs assessment, training in digital content creation, the use of social media platforms (Instagram, Facebook, TikTok), e-commerce platforms (Shopee, Tokopedia, and local marketplaces), as well as branding strategy implementation. The results of the program indicate increased awareness among SME participants regarding the importance of digital marketing, a higher number of SMEs actively marketing their products online, and improved interaction and engagement on digital platforms. Digital marketing assistance has proven effective in strengthening SME competitiveness and expanding market access, particularly for business actors in semi-rural areas such as Lumbir Subdistrict.